Erbin Regulates Tissue Factors Through Ras/Raf Pathway in Coagulation Disorders in Sepsis - Yang C; Lei C; Jing G; Xia Y; Zhou H; Wu D; Zuo J; Gong H; Wang X; Dong Y; Aidebaike D; Wu X; et al. (Journal of Inflammation Research)
Cheng Yang,1,* Chuntian Lei,1,* Guoqing Jing,1 Yun Xia,1 Huimin Zhou,1 Die Wu,1 Jing Zuo,1 Hailong Gong,1 Xing Wang,1 Yingyue Dong,1 Delida Aidebaike,1 Xiaojing Wu,2 Xuemin Song1 1Research Centre of Anesthesiology and Critical Care Medicine, Zhongnan Hospital of Wuhan University, Wuhan, Hubei Province, 430062, People’s Republic of China; 2Department of Anesthesiology, Renmin Hospital of Wuhan University, Wuhan, Hubei Province, 430060, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaojing Wu; Xuemin Song, Email RM000851@whu.edu.cn; xueminsong@whu.edu.cnBackground: Sepsis, as a clinically critical disease, usually induces coagulation disorders. It has been reported that ERBB2 Interacting Protein (Erbin) is involved in the development of various inflammatory diseases, and macrophages are involved in the regulation of coagulation disorders in sepsis. However, the role of Erbin in coagulation disorders in sepsis and the relationship between Erbin and macrophage regulation of coagulation function are still unclear.Methods: At the cellular level, macrophages were treated with lipopolysaccharide (LPS) or MEK inhibitor (PD98059), protein expression levels were detected by Western blot, co-immunoprecipitation (Co-IP), and immunofluorescence, mRNA expression levels were detected by quantitative real-time polymerase chain reaction (qPCR), and the concentration of tissue factor (TF) in cell supernatant was detected by enzyme linked immunosorbent assay (ELISA). At the animal level, the cecal ligation and perforation (CLP) model was constructed in mice, and the inflammatory response and coagulation disorder of mice were observed by hematoxylin-eosin (HE) staining, immunohistochemistry, ELISA, and automatic hemagglutination analyzer. The protein and mRNA expression level were detected by Western blot and qPCR. Pearson linear correlation analysis was used to analyze the correlation between the inflammation index and the coagulation function index.Results: We confirmed that the Erbin is involved in the regulation of coagulation function by macrophages and plays a role in the coagulation disorder of sepsis. In vivo studies have shown that mice with Erbin deletion have more obvious enhanced coagulation function, and in vitro studies have shown that Erbin knockout mediated macrophage secretion of TF by activating the Ras/Raf pathway.Conclusion: Erbin reduces the coagulation activation by inhibiting TF release from macrophages.Keywords: Erbin, coagulation disorders, sepsis, tissue factor, macrophage